Uncovering the hidden RNA virus diversity in Lake Nam Co: Evolutionary insights from an extreme high-altitude environment - Lilin Wu; Yongqin Liu; Wenqing Shi; Tianyi Chang; Pengfei Liu; Keshao Liu; Yong He; Zhaorong Li; Mang Shi; Nianzhi Jiao; Andrew S. Lang; Xiyang Dong; et al. (Proceedings of the National Academy of Sciences, 2025)
Alpine lakes, characterized by isolation, low temperatures, oligotrophic conditions, and intense ultraviolet radiation, remain a poorly explored ecosystem for RNA viruses. Here, we present the first comprehensive metatranscriptomic study of RNA viruses in Lake Nam Co, a high-altitude alkaline saline lake on the Tibetan Plateau. Using a combination of sequence- and structure-based homology searches, we identified 742 RNA virus species, including 383 novel genus-level groups and 84 novel family-level groups exclusively found in Lake Nam Co. These findings significantly expand the known diversity of the Orthornavirae , uncovering evolutionary adaptations such as permutated RNA-dependent RNA polymerase motifs and distinct RNA secondary structures. Notably, 14 additional RNA virus families potentially infecting prokaryotes were predicted, broadening the known host range of RNA viruses and questioning the traditional assumption that RNA viruses predominantly target eukaryotes. The presence of auxiliary metabolic genes in viral genomes suggested that RNA viruses (families f . 0102 and Nam-Co_family_51) exploit host energy production mechanisms in energy-limited alpine lakes. Low nucleotide diversity, single nucleotide polymorphism frequencies, and pN/pS ratios indicate strong purifying selection in Nam Co viral populations. Our findings offer insights into RNA virus evolution and ecology, highlighting the importance of extreme environments in uncovering hidden viral diversity and further shed light into their potential ecological implications, particularly in the context of climate change.